Characterization and Diversity Assessment of Nepalese Garlic (Allium sativum L.) Landraces - Thapa, P.; Manali, R. P.; Karkee, A.; Ghimire, K. H.; Joshi, B. K.; Mishra, K. K. (Journal of Agriculture and Environment, 2021)
A research was carried out at the field of National Agriculture Genetic Resources Centre (NAGRC), Khumaltar, Lalitpur, Nepal in 2019 with the objective of phenotypic characterization and genetic diversity assessment of thirty-seven local garlic landraces. The phenotypic diversity was assessed based on fifteen qualitative and nine quantitative characters by sing non replicated rod row design following the descriptors developed by IPGRI, 2001. Descriptive statistics were calculated by using MS Excel 2016 and UPGMA clustering and PCA was done with MINITAB-17. The diversity index (H’) and coefficient of variation for different traits ranged from 0.54-0.96 and 16.89-87.85, respectively. Four clusters identified and CO 10307, CO 10482 and CO 10615 of fourth clusters were superior in terms of quantitative characters. Five principal components contributed95.2% of the cumulative variance. This result will be helpful for breeder and researchers to comprehensively understand the agro-morphological characters as well as diversity of the Nepalese garlic collection.